How do attached crown parts and branches contribute to the diversity of saproxylic fungi and beetles in downed and decaying spruce trees? - Korhonen, Aku; Siitonen, Juha; Hamberg, Leena (Springer Nature, 2025)
A significant proportion of forest-dwelling species in boreal forests are saproxylic, i.e., dependent on deadwood. To safeguard deadwood-associated diversity in managed forest landscapes, it is important to understand how substrate preferences and specialization structure saproxylic species communities across different deadwood resource types. In this study, we investigated the diversity and associations of saproxylic fungi and beetles at the scale of entire trees to understand how different tree parts contribute to species diversity. To do this, we sampled species assemblages in trunks (d > 15 cm), tops (d 5–10 cm) and branches (d < 5 cm) of 31 fallen Norway spruce trees. Fungal assemblages were investigated with DNA metabarcoding from wood samples, and beetles were surveyed by bark peeling and sieving. Our results showed that, fungal and beetle assemblages were clearly differentiated between trunks and branches. In the tops, fungal community composition was intermediate between trunks and branches, whereas beetle species composition was more closely aligned with trunks. Trunks and branches both harbored specialized fungal and beetle species, but no species were identified as specialists of tops. Fungal and beetle richness were lowest in branches, and fungal richness peaked in tops. Substrate specialization of saproxylic species at the scale of individual trees imply that deadwood restoration in managed forests should prioritize whole-tree retention instead of partial retention such as artificial high stumps or pruned logs.
Keywords: lahopuut; lahottajasienet; kovakuoriaiset; dead wood; fine woody debris; wood-inhabiting fungi; Coleoptera; metabarcoding; boreal forest